A nurse‐led implantable loop recorder service is safe and cost effective. (9th October 2019) - Lim, Wei Yao; Papageorgiou, Nikolaos; Sukumar, Shivasankar M.; Alexiou, Sophia; Srinivasan, Neil T.; Monkhouse, Christopher; Daw, Holly; Caldeira, Helder; Harvie, Helen; Kuriakose, Jincymol; Baca, Marco; Ahsan, Syed Y.; et al.
Abstract: Introduction: Implantable loop recorders (ILR) are predominantly implanted by cardiologists in the catheter laboratory. We developed a nurse‐delivered service for the implantation of LINQ (Medtronic; Minnesota) ILRs in the outpatient setting. This study compared the safety and cost‐effectiveness of the introduction of this nurse‐delivered ILR service with contemporaneous physician‐led procedures. Methods: Consecutive patients undergoing an ILR at our institution between 1st July 2016 and 4th June 2018 were included. Data were prospectively entered into a computerized database, which was retrospectively analyzed. Results: A total of 475 patients underwent ILR implantation, 271 (57%) of these were implanted by physicians in the catheter laboratory and 204 (43%) by nurses in the outpatient setting. Six complications occurred in physician‐implants and two in nurse‐implants ( P  = .3). Procedural time for physician‐implants (13.4 ± 8.0 minutes) and nurse‐implants (14.2 ± 10.1 minutes) were comparable ( P  = .98). The procedural cost was estimated as £576.02 for physician‐implants against £279.95 with nurse‐implants, equating to a 57.3% cost reduction. In our center, the total cost of ILR implantation in the catheter laboratory by physicians was £10 513.13 p.a. vs £6661.55 p.a. with a nurse‐delivered model. When overheads for running, cleaning, and maintaining were accounted for, we estimated a saving of £68 685.75 was performed by moving to a nurse‐delivered model for ILR implants. Over 133 catheter laboratory and implanting physician hours were saved and utilized for other more complex procedures. Conclusion: ILR implantation in the outpatient setting by suitably trained nurses is safe and leads to significant financial savings.